High-Risk Screening and Diagnosis of Inborn Errors of Metabolism: A Practical Guide for Laboratories. (6th August 2018) - Civallero, Gabriel; de Kremer, Raquel; Giugliani, Roberto
Inborn errors of metabolism (IEM) are a large and heterogeneous group of genetic diseases. In most of these conditions, the presence of variants in specific genes leads to enzyme deficiencies that affect a particular metabolic step. The number of laboratories dedicated to the study of IEM is very limited worldwide, and its multiplication is urgently required for a more effective diagnosis. With the scarcity of specialized centers, the diagnosis of affected individuals comes too late or does not happen at all. Moreover, the biological samples have to travel long distances, compromising its quality and delaying still more the diagnosis. In this work, we suggest a practical guide for a basic biochemical laboratory to get involved in the study of IEM. This proposal was based on already described metabolic tests and involves the need of just a few, simple, and affordable instruments that can give an enormous quantity of information about the possible metabolic defect faced, such as a spectrophotofluorometer and a gas chromatography/mass spectrometry (GC/MS) instrument. The procedures proposed can be customized and adapted to particular needs and situations, which make it especially useful for developing countries.